La representación del cuerpo dócil en El Infierno Verde de José Marín Cañas - González Muñoz, Irene (2014)
In the framework of research journey "Literary Representations of the Body", the objective of this article on the novel El infierno verde, of José Marín Cañas, is to demonstrate how the human body is represented in the context of war. For this, some of the proposals of Michel Foucault in Discipline and Punish and History of Sexuality, texts in which the author presents the body as the central element from which it is founded and practically symbolic social order are used.